The contribution of migration to economics growth: Evidence from Spain - Antonio Mihi-Ramírez; Sara Ojeda-González; María José Miranda-Martel; Eugene Agoh (Open Economics, 2018)
Productivity is crucial for economic growth. In a time of challenges such as the population ageing, a growing migration flows and slowdown of the economy it is very important to know the impact of migrant workers in productivity and development. Therefore, this paper studies relevant migration theories and the evolution of migration flows, productivity and their effect on economic growth. We analyse the contribution of immigrants' workers to productivity, to the employment rate and to the demography of Spain in the last 10 years, a country where the last crisis deeply changes the migration patterns and economic conditions. The results show that, in this case, the impact of immigration on the level of development was small but positive.
Keywords: F22; J24; 330; GDP growth; immigrant workers in Spain; labour input; labour productivity of immigrants; total hours worked